The Positive Concept of The Glad Game as Reflected in Eleanor Hodgam Porter’s Pollyanna - Helmita, Helmita; Gaho, Kurniawati (Jurnal Ilmiah Langue and Parole, 2024)
The title of this research is "Positive Concepts of Joyful Play as reflected in the novel Pollyanna by Eleanor Hodgmam Porter". The problem of this research is focused on Pollyanna's personality using Freud's theory, external conflict using Jones' theory, as well as the moral message contained in Pollyanna's character using Nurgiyantoro theory which is reflected in Pollyanna's novel. This research is a qualitative descriptive research. The method used in this research is descriptive qualitative. The approach used in this research is literary psychology. The technique used in this research is literature. To obtain certain data by searching and collecting several books related to personality analysis, external conflict, and moral messages in a literary work. By quoting sentences or words that show personality, external conflicts, and moral messages and then describe them. Pollyanna's personality includes three parts, namely Id, Ego, and Superego. The Id personality arises because it is influenced by thoughts that want to please itself, the Ego arises because Pollyanna is in a dilemma between thinking about two things at once and she doesn't know which one to choose, while the Superego grows because she is more concerned with the interests of others than herself. Pollyanna's external conflict occurred between herself and her aunt because basically her aunt didn't want her and really hated her. The moral message shown by Pollyanna in the novel includes four parts, namely, being honest, being yourself, being responsible, having moral courage, being humble, and being critical.